Breaking Dormancy of Shallot (Allium ascolonicum L.) Bulb Using Hydrogen Peroxide - Nurfaida, Nurfaida; Syam'un, Elkawakib; Ulfa, Fachirah; Mantja, Katriani; Faried, Muhammad (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Shallot bulbs have a dormancy period, so they must be stored for 3-4 months. This condition inhibits the acceleration of planting, which has a short time, so efforts are needed to accelerate the dormancy period by using hydrogen peroxide. This research was carried out from June to July 2023 at the Screen House, Teaching Farm, Faculty of Agriculture, Hasanuddin University. The study was arranged in a randomized block design with a two-factor factorial design. The first factor is the variety of Mentes, Rubaru, Violetta 2 Agrihorti, Kramat 1, and Ambassador 3 Agrihorti. The second factor is hydrogen peroxide concentration with three levels, namely 0%, 10% and 20%. The results showed that breaking the dormancy of shallot bulbs using hydrogen peroxide at a concentration of 20% effectively triggered the process of bulb growth in the various shallot varieties tested, marked by an increase in the percentage of rooted and sprouted bulbs. The Rubaru and Mentes varieties had an excellent response to 20% hydrogen peroxide immersion, indicated by a shorter rooting and sprouting time, compared to other varieties and concentrations of hydrogen peroxide. Therefore, hydrogen peroxide with a concentration of 20% can be used to break dormancy in shallot bulbs. However, further studies are needed on growth and production in the field and the quality and safety of shallot bulbs. Keywords: Bulb, Dormancy, Hydrogen peroxide, Shallot.